Evaluation of the quality characteristics of fermented sausages and sausage-like products sold in kars - Çiğdem Sezer; Aksem Aksoy; Özgür Çelebi; Turgay Deprem; Metin Öğün; Nebahat Bilge Oral; Leyla Vatansever; Abamüslüm Güven (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted for the purpose of identifying the microbiological, physico-chemical and histological aspects of quality criteria in sausage-like products obtained from local markets and different samples of fermented sausages produced using traditional methods by local butcher shops in the province of Kars. Materials and Methods: Sampling was made during just one day and all the fermented sausages (n:30) and cooked sausage-like products (n:10) were purchased from all butchers and market points in Kars city centre. Microbiological analysis was performed by spread and/or pour plate techniques. Histological analysis was performed by Crossman triple stain and hematoxylin-eosin stains. Physicochemical analysis was performed by gravimetric and spectrophotometric methods. Results: Escherichia coli was identified in one of the cooked sausagelike products and in one sample of fermented sausage. Neither Clostridium perfringens nor E. coli O157:H7 were identified in any of the samples. Listeria monocytogenes was isolated in four (10%) of the fermented sausage samples and Salmonella spp in two fermented sausage samples (5%). Nitrate and nitrite levels in the sausage were found to be 14.88–943.71 mg/kg and 0.46-378.16 mg/kg, respectively. Thirteen (32.5%) of the sausage samples that were examined contained epithelial tissue, 27.5% (11 samples) contained glandular epithelial tissue, which was mostly seromucous in nature, and five (12.5%) contained cartilage and bone tissue with smooth muscle tissue. Conclusion: None of the sausage samples met the requirements of the standards. This shows that controlled production and post-production inspection are very important.